O pensamento liberal e sua expressão na concepção educacional de Anísio Spínola Teixeira na década de 1930 no Brasil - Meurer, Adriéle Cristina de Souza (2012)
This study investigated the educational thought of Anísio Teixeira Spinola (1900-1970), a leading Brazilian educators and disciple of John Dewey (1859-1952). It is presented initially in the first chapter the process of consolidation of the capitalist mode of production and liberalism as its founding ideology. It was, therefore, the path of liberalism, its principles and its expression in the educational thought of John Dewey and, consequently, the educational thought of Teixeira, in the 1930s in Brazil. To understand the thinking of John Dewey, studied the works of Liberalism, Freedom and Culture (1970), Experience and Education (1979b / 1980), Democracy and Education (1979), fundamental for the understanding of the relationship between liberal principles and their educational proposal, since it is considered the greatest exponent of the escolanovismo and expression of liberal ideology in education. To investigate the expression of liberal thought in the work of Teixeira, we studied the works Small Introduction to Philosophy of Education (1975); In march for Democracy (1934) and Education for Democracy (1997), written in the mid , 1930. It found the expression of liberal principles of equality, freedom, individuality, ownership and democracy in educational proposal for Teixeira, Brazil in the 1930s, as regards the conception of science, intelligence and experience.